2011
DOI: 10.1002/hep.24639
|View full text |Cite
|
Sign up to set email alerts
|

Tenascin-C: A novel mediator of hepatic ischemia and reperfusion injury

Abstract: Hepatic ischemia/reperfusion (IRI) injury remains a major challenge in clinical orthotopic liver transplantation (OLT). Tenascin-C (Tnc) is an extracellular matrix protein (ECM) involved in various aspects of immunity and tissue injury. Using a Tnc-deficient mouse model, we present data that suggest an active role for Tnc in liver IRI. We show that Tnc-deficient mice have a reduction in liver damage and a significant improvement in liver regeneration after IRI. The inability of Tnc−/− mice to express tenascin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 50 publications
1
50
0
1
Order By: Relevance
“…Expression levels of each protein are expressed as a ratio of β-tubulin levels for normalization and as mean±standard deviation. P value, ANOVA MAPK-independent pathways [34], while TNC may stimulate synthesis of IL-1β [35]. The positive feedback mechanisms between TNC and IL-1β may cause post-SAH BBB disruption.…”
Section: Discussionmentioning
confidence: 99%
“…Expression levels of each protein are expressed as a ratio of β-tubulin levels for normalization and as mean±standard deviation. P value, ANOVA MAPK-independent pathways [34], while TNC may stimulate synthesis of IL-1β [35]. The positive feedback mechanisms between TNC and IL-1β may cause post-SAH BBB disruption.…”
Section: Discussionmentioning
confidence: 99%
“…12,14 In addition, TNKO mice showed a marked decrease in expressions of inflammatory cytokines and MMP-9 after hepatic ischemia and reperfusion. 15 This study first demonstrated the link between TNC induction and MMP-9 upregulation or BBB disruption in the brain following SAH by using TNKO mice and exogenous TNC treatment. Although it remains unknown how TNC upregulates MMP-9, TNC induces MAPKs, 8,15 which are known to upregulate MMP-9.…”
Section: Discussionmentioning
confidence: 99%
“…15 This study first demonstrated the link between TNC induction and MMP-9 upregulation or BBB disruption in the brain following SAH by using TNKO mice and exogenous TNC treatment. Although it remains unknown how TNC upregulates MMP-9, TNC induces MAPKs, 8,15 which are known to upregulate MMP-9. 4 Because this study also demonstrated that TNC regulated MAPK activation in brain capillary endothelial cells, it may be reasonable to consider that TNC induces MMP-9 and causes BBB disruption in mice with SAH via MAPK activation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations